The Implementation of the SSCS (Search, Solve, Create, and Share) Learning Model in Qira'ah Instruction - Nurhasanah; Wasilah; Kemas Muhammad (The Future of Education Journal, 2025)
This research is motivated by students' needs for a variety of learning models. Arabic language learning at the junior high school level, particularly in reading skills (qirā’ah), is often still conventional, relying heavily on translation and teacher-centered instruction. This research aims to examine the effectiveness of the Search, Solve, Create, and Share (SSCS) learning model in enhancing qirā’ah skills among seventh-grade students at SMP IT Fathona Palembang. The study employs a mixed-method approach, combining quantitative (pre-test and post-test) and qualitative (observation and interviews) data. The experimental design used is pre-experimental with one group pre-test–post-test design. Fifteen students were selected purposively as the research sample. The results showed a significant increase in students’ average scores from 33.33 (pre-test) to 83.33 (post-test). Normality and homogeneity tests confirmed the appropriateness of the data for parametric analysis, and a paired sample t-test showed a significant difference (Sig. 0.000 < 0.05), indicating that the SSCS model was effective. Qualitative findings from interviews revealed that students found the learning process more engaging and collaborative through the SSCS stages. They felt more motivated and better understood Arabic texts when involved in searching for information, solving problems, creating content, and sharing outcomes. This study contributes to expanding the application of the SSCS model to language learning contexts, especially in Islamic junior high schools. However, it is limited by the small sample size, suggesting that future studies should explore broader settings and additional language skills.